Cognitive Distortion And Its Relationship To The Stressful Life Events Of Iraqi University Students - Younus Abed, Amjad (Opción, 2019)
The current research aims to identify: • The level of cognitive distortion among Iraqi University students. • The significance of the differences in the level of cognitive distortion among Iraqi university students according to the two sex variables (male - female) and specialization (scientific - human) • Stressful life events for Iraqi University students. • The significance of the differences in life stressful events for Iraqi University students according to the two sex varia- bles (male - female) and specialization (scientific - human). • The correlation between cognitive distortion and stressful life events among Iraqi universi- ty students. The sample of the research consisted of (200) male and female students from the faculties of the Iraqi University, and they were chosen in the simple random stratified method of equal selection, and the researcher adopted a scale (Eureka and Daytomaso, 2001) to measure cognitive distor- tion, and a scale (Sultan, 2009) to measure stressful life events, After analyzing the results by using the statistical bag (SPSS), the most important results were as follows: 1- Iraqi University students have a low level of cognitive distortion. 2- There are no statistically significant differences in the level of cognitive dis- tortion among Iraqi University students according to the variables of gender and specialization. 3- The high exposure of Iraqi university students to stress- ful life events. 4- There are no statistically significant differences in stressful life events for Iraqi university students according to the gender variable, while there are no statistically significant differences in stressful life events for Iraqi university students according to the specialty variable. 5- There is a statistically significant correlation between cognitive distortion and stressful life events among Iraqi University students.The researcher came out with a set of conclusions, recommendations and proposals. Cognitive distortion and its relationship to the stressful life events of Iraqi University students